The relationship between musical sophistication, executive functions and autistic traits - Chee, Zhong Jian (2023)
The overarching goal of this thesis is to examine how musical sophistication and/or specific dimension of musical sophistication are related to autistic traits, EF and quality of life in the general population. Chapters 2 and 3 focus on validating the AQ as the AQ was used throughout the studies of the thesis. Chapter 2 investigated whether language influences the response to the AQ among multilingual Malaysians. Specifically, participants’ responses to the AQ in their native language and English were compared. Chapter 3 examined the psychometric properties of an abridged version of the AQ (i.e., AQ-28) in the Dutch and Malaysian general population, and whether the autistic traits as measured by the AQ-28 are comparable between Dutch and Malaysian participants. Chapter 4 investigated if autistic traits would be associated with certain music preferences after controlling for other factors (e.g., age, gender, personality traits and musical ability) that are known to influence music preferences. Chapter 5 explored if listening to preferred music would improve the performance on EF tasks compared to relaxing music and silence and whether autistic traits and EDA are associated with the performance on EF tasks. The relationship between autistic traits, musical sophistication, EF, and quality of life was examined in Chapter 6.